(untitled) (Revista de Ciências Agroveterinárias, 2012)
This study aimed to determine the efficiency of the removal of cadmium by natural zeolite available in the region of Southern Brazil (zeolite basalt - ZB) comparing its performance with a commercial zeolite imported from Cuba (ZC). The exchange capacity of zeolite materials was determined by the Kitsopoulos (1999) method. The effect of pH on removal of Cd was measured at pH 3.0, 4.0 and 5.0 (±0.2) and initial concentrations of 20 and 500 mg L-1. The competition between Cd and Cr was determined in the initial concentration of 20 mg kg-1 of Cd and Cr and pH 4.0 and 5.0. The maximum removal of cadmium was assessed at pH 4.0 and the initial concentrations of 20, 40, 80, 120, 200 and 500 mg L-1. Quantification of cadmium and chromium was carried out by atomic absorption spectrometry with flame atomisation system type air-acetylene. To test the average percentage of removed Cd+2 and Cr+3 at different pH values we used the Scott-Knott 5% significance level. The increase in pH from 3.0 to 4.0 for increased removal of ZC and ZB Cd that occurred on increasing the pH from 4.0 to 5.0. The ZC showed higher removal at pH 4.0 and pH 5.0 in ZB. The highest percentage was desorbed for ZB initial concentration 500 mg L-1. The competitive removal was more significant for chromium. The maximum removal of Cd was calculated to 3433 mg kg-1 for ZC and 1387 mg kg-1 for ZB.